Imágenes y paisajes : el arte rupestre del Noreste de Catamarca, Argentina - Calomino, Eva Amanda (Access archaeology., 2019)
Northeast of Catamarca, Argentina, there is a set of shelters and caves located in the rainforest with rock art with virtually no background. This book presents a study and systematic analysis of the plastic-thematic-compositional repertoire of the rock art sites of 'Los Algarrobales' and their spatial and temporal distribution.